Validity of microrubri, instrument to measure the development of competences in mathematics (2019)
The article presents the validity and reliability of the MICRORUBRI instrument based on rubrics, with problems applied to engineering that allow analyzing situations in real context, as well as the generation, visualization of surfaces, planes and vectors; its objective is to evaluate the development of competences in vector calculus in students who are enrolled in undergraduate engineering programs in the Municipality of Cúcuta, Colombia. It follows a design of descriptive study of validation of multidimensional scales through factorial analysis, construct validity, and facial. The study population was students of undergraduate programs of engineering, administration and agricultural sciences with ages between 17 and 20 years in the city of Cúcuta, Colombia, constituted the sample by 500 students. Results: A scale of 35 items was obtained. The factor analysis revealed dimensions of pedagogical practice oriented to leadership, creative thinking, emotional satisfaction, independence, creative attitude, productivity, leadership competencies, motivation; internal consistency was adequate (Cronbach alpha 0.72 – 0.95), global intraclass correlation coefficient of 0.97, average differences in sum of items -1.2 (SD: 7.5) and Kappa indexes higher than 0.9, shows high agreement among experts. Conclusion: MICRORUBRI is a valid and reliable instrument to evaluate the development of competences.